The Use of the Quizizz Application as a Learning Evaluation Tool for Grade XI 'Merdeka' Curriculum Students in the History Subject at SMA Negeri 5 Palu - Moh Safi Rizki; Hasan Hasan; Juraid Juraid; Ika Nurjayanti (FKIP - Universitas Riau, 2026)
This study was conducted in response to the need for more engaging history learning evaluations and the limited research on the use of Quizizz as an evaluation tool in senior high school history classes. This study aims to determine the use of the Quizizz application as a learning evaluation tool for Grade XI Merdeka students in History at SMA Negeri 5 Palu and to examine students' perceptions of its use. This study employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The research participants consisted of 1 school principal, 1 vice principal for curriculum, 1 history teacher, and 10 Grade XI Merdeka students who had previously participated in history lessons using the Quizizz application. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that the use of Quizizz as a learning evaluation tool effectively increased students' motivation, interest, and engagement in the learning process. Its interactive quiz features, automatic scoring, and immediate feedback helped students better understand the material and identify their mistakes. Students expressed positive perceptions because Quizizz made the assessment process more engaging, enjoyable, and less monotonous. Despite internet connectivity constraints, Quizizz was still considered an effective learning evaluation tool for history learning.